Waste Management Ecotourism Drives Local Community Environmental Awareness And Participation: Ekowisata Pengelolaan Sampah Mendorong Kesadaran Dan Partisipasi Lingkungan Masyarakat Lokal - Hani Agustina; Yosef Abdul Ghani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The continuous expansion of the tourism sector significantly escalates ecological pressures, particularly concerning garbage accumulation in destination areas. Specific Background Sustainable recreational models, such as Udjo Ecoland, attempt to balance tourist activities with ecological preservation by implementing reduce, reuse, and recycle principles. Knowledge Gap While extensive literature examines visitor behavior, comprehensive studies focusing on how garbage-centric governance shapes the ecological consciousness of resident populations remain limited. Aims This qualitative descriptive research investigates the governance of garbage-centric recreational destinations at Udjo Ecoland and its role in building ecological consciousness among resident populations. Results Findings from observations and interviews reveal that integrating cultural education with direct public involvement in garbage sorting and plastic reduction fosters responsible ecological habits. Furthermore, adequate sanitation facilities positively shape visitor perceptions and behaviors toward destination cleanliness. Novelty This study highlights that garbage-centric recreational governance serves not solely as a sustainable destination strategy, but crucially functions as an active empowerment platform for transforming public ecological behaviors. Implications Destination managers and policymakers must prioritize collaborative, stakeholder-driven sanitation governance models to ensure long-term ecological sustainability and continuous public empowerment. Highlights Integrating cultural education with ecological preservation successfully transforms public habits regarding sanitation. Applying reduce, reuse, and recycle principles minimizes plastic usage and promotes responsible garbage sorting. Adequate hygiene facilities positively shape visitor behavior and perceptions regarding destination cleanliness. Keywords Sustainable Tourism; Ecological Preservation; Garbage Sorting; Destination Management; Stakeholder Collaboration